Personalities portraits gallery in the history of Romania, Moldova and other countries (Confluenţe Bibliologice, 2025)
The article is about reproductions of the most representative ﬁgures in the history of Romania, Moldova, France, USA, Russia etc. painted by painters and anonymous master. The paintings represent diﬀerent periods of history.
Keywords: historical personality; Romanian personalities